276 Impact of pre-farrow feeding amount and timing on stillborn rate of sows. (30th November 2020) - Miller, Kayla; Kellner, Trey A
Abstract: Pre-farrowing feeding allowance and timing are often based on logistical ease instead of optimizing farrowing performance. The objective of this experiment was to decrease the stillborn rate via the amount and timing of feeding prior to farrowing. A total of 245 PIC 1050 (PIC, Inc., Hendersonville, TN) individually housed bred females were randomly allotted to 1 of 3 treatments on d 0. The 3 pre-farrow feeding treatments consisted of: 1) 2 meals of 0.9 kg fed at 630 h and 1530 h; 2) 1 meal of 1.8 kg fed at 630 h; and 3) 2 meals of 2.7 kg fed at 630 h and 1530 h. Dietary treatment commenced on entry into the farrowing crate and continued until they farrowed (ranged from d 2 to d 10). Data were analyzed using Proc MIXED (SAS 9.4; Cary, NC) with treatment as the main effect and sow as the experimental unit. Females having a litter with a total born ≤ 11 or ≥ 21 or did not consume their allotted feed were considered outliers and were removed from the statistical analysis. Feeding 2 meals of 0.9 kg per day trended to reduce stillborn rate compared to the other 2 pre-farrow feeding treatments (2 meals of 0.9 kg = 5.6%, 1 meal of 1.8 kg = 8.6%, 2 meals of 2.7 kg = 9.0%; P = 0.090). Pre-farrow feeding amount and time had no impact on total born or mummies (P ≥ 0.270). As a bonus, feeding small meals multiple times a day will reduce the farm's overall feed cost compared to providing full feed access pre-farrow. In conclusion, implementation of a pre-farrowing feeding strategy is a vehicle that can be used to reduce the stillborn rate in commercial production.